When all doors close: Implications of COVID-19 for cosmopolitan entrepreneurs - Niina Nummela; Eriikka Paavilainen-Mäntymäki; Riikka Harikkala-Laihinen; Johanna Raitis (Sage, 2022)
The emergence of the COVID-19 pandemic is an external shock that has disrupted the foundations of everyday life. For cosmopolitan entrepreneurs, the impact is even more decisive as it confronts their core values and jeopardises their identities, ways of working and the lifestyles they cherish. Cosmopolitans are individuals who identify themselves as citizens of the world and voluntarily move from country to country in pursuit of self-fulfilment in both life and work. Cosmopolitan entrepreneurs are future-oriented and open to the world and the opportunities it may provide. Beyond securing, maintaining and improving their professional and/or economic positions, their mobility is an elementary part of the cosmopolitan life itself, something they find attractive, interesting and stimulating. Thus, a cosmopolitan entrepreneur’s business is often non-location-bound to enable continued mobility. With our interview-based research, we shed light on how COVID-19 has changed the lives of Finnish-born cosmopolitan entrepreneurs, discussing what they feel about the changes and how they see their future.